The Effectiveness Of Pre-Planting Seeds Bio-Matriconditioning And Application Of Fertilization With Leisa Technique On Growth Of Areca Nut Seedling (Areca Catechu L.) - Gusti Ayu Kade Sutariati; Muhidin; Nini Mila Rahni; Gusti Ngurah Adi Wibawa; La Mudi (International Journal of Science, Technology & Management, 2021)
Areca nut is widely used as industrial raw material, both for health and cosmetics and as a source of renewable energy. This study aimed to examine the combination of seed bombatriconditioning and LEISA fertilization treatments that were effective in increasing the growth of areca nut seedlings. The research was carried out in the Wua-Wua Kendari Village, from March to July 2021. The study used a split-plot design with a completely randomized design (CRD). The main plot is seed biomatriconditioning treatment which consists of 3 treatments. While the subplots were fertilized with the LEISA technique which consisted of 6 treatments so that 18 treatment combinations were obtained with 3 replications. Observations were made on plant height, number of leaves, stem diameter, number of roots, wet weight and dry weight of shoot. Observational data were analyzed using analysis of variance, followed by the DMRT ?0.05 if there was a significant effect. The results showed that seed biomatriconditioning treatment with rhizobacteria integrated with the LEISA technique was able to increase the growth of areca nut seedlings. The integration between L1R biomatriconditioning and the application of organic plus fertilizer + 100% inorganic fertilizer showed a better growth performance of areca nut on plant height, number of leaves, stem diameter, number of roots, wet weight and dry weight of betel nut which were significantly different with control and application 100% inorganic fertilizer, but not significantly different from organic plus fertilizer, organic plus fertilizer + 50% inorganic fertilizer and organic plus fertilizer + 25% inorganic fertilizer. As a conclusion, pre-planting seed treatment with L1R biomatriconditioning is very important to increase areca nut seed germination. To increase the growth of areca nut seedlings, further fertilization needs to be done with organic plus fertilizer or a combination of organic plus fertilizer + 25% inorganic fertilizer.